Delta Power Is Higher and More Symmetrical in Ischemic Stroke Patients with Cortical Involvement - Fanciullacci, Chiara; Bertolucci, Federica; Lamola, Giuseppe; Panarese, Alessandro; Artoni, Fiorenzo; Micera, Silvestro; Rossi, Bruno; Chisari, Carmelo (Frontiers in Human Neuroscience, 2017)
A brain injury resulting from unilateral stroke critically alters brain functionality and the complex balance within the cortical activity. Such modifications may critically depend on lesion location and cortical involvement. Indeed, recent findings pointed out the necessity of applying a stratification based on lesion location when investigating inter-hemispheric balance in stroke. Here, we tested whether cortical involvement could imply differences in band-specific activity and brain symmetry in post stroke patients with cortico-subcortical and subcortical strokes. We explored brain activity related to lesion location through EEG power analysis and quantitative EEG (qEEG) measures. Thirty stroke patients in the subacute phase and 10 neurologically intact age-matched right-handed subjects were enrolled. Stroke patients were equally subdivided in two groups based on lesion location: cortico-subcortical (CS, mean age ± SD: 72.21 ± 10.97 years; time since stroke ± SD: 31.14 ± 11.73 days) and subcortical (S, mean age ± SD: 68.92 ± 10.001 years; time since stroke ± SD: 26.93 ± 13.08 days) group. We assessed patients’ neurological status by means of NIH Stroke Scale (NIHSS). High density EEG at rest was recorded and power spectral analysis in Delta (1-4 Hz) and Alpha (8-14 Hz) bands was performed. Quantitative EEG metrics as pairwise derived Brain Symmetry Index (pdBSI) and Delta/Alpha Ratio (DAR) were computed and correlated with NIHSS score. S showed a lower Delta power in the unaffected hemisphere compared to affected hemisphere (z= -1.98, p<0.05) and a higher Alpha power compared to CS (z= -2.18, p<0.05). pdBSI was negatively correlated with NIHSS (R= -0.59, p<0.05). CS showed a higher value and symmetrical distribution of Delta band activity (z= -2.37, p<0.05), confirmed also by a higher DAR value compared to S (z= -2.48, p<0.05). Patients with cortico-subcortical and subcortical lesions show different brain symmetry in the subacute phase. Interestingly, in subcortical stroke patient brain activity is related with the clinical function. Quantitative EEG measures can be explicative of brain activity related to lesion location and they could allow precise definition of diagnostic-therapeutic algorithms in stroke patients.